(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, a linear perturbation up to any order in ε for a cubic center with a multiple line of critical points is considered. By the algorithm of any order Melnikov function, the sharp upper bound of the number of limit cycles is 2.